Reagindo ao hip-hop no youtube: análise etnográfica sobre os vídeos de reação do movimento hip-hop - Van Der Sand, João Pedro Pacheco (2021)
The theme of this dissertation comprehends reaction videos about rap and funk on the YouTube platform. It is an emerging audiovisual genre, native to this platform, in which content producers exhibit their reactions to various cultural assets. Supported by the ethnography approach for the internet (Hine, 2015), I propose an analysis of the cultural senses articulated by content producers who dedicate themselves to productions of this type. The theoretical foundation seeks to present the definitions already established about this audiovisual genre, as well as a contextualization of its emergency conditions in a platform society (Pasquale, 2015; Van Djick, 2018). From this theoretical approach, which also contemplates the tendencies of a participatory culture, I argue with Miller (2013; 2019) that funk and rap reaction videos are configured as a cultural genre for consumption on YouTube. To the theorical approach, it is added a survey of Brazilian academic production on hip-hop culture in the country, also proposing a look at the technological appropriations that are structuring this cultural aspect. With an ethnographic approach, I followed four content producers who are mainly dedicated to the production of reaction videos. Thus, I described and interpreted the main cultural meanings linked to their practices in an ethnographic perspective. The results reveal that, through a performance dimension (Hennion, 2010; Goffman, 1985) that involves corporeality and expression of taste, reaction videos articulate meanings of company, curation and pedagogy.